Unrealized diversity in an urban rainforest: A new species of Lygosoma (Squamata: Scincidae) from western Sarawak, Malaysia (Borneo) - Karin, Benjamin R.; Freitas, Elyse S.; Shonleben, Samuel; Grismer, Lee Lee; Bauer, Aaron Matthew; Das, Indraneil (Magnolia Press, 2018)
We collected two specimens of an undescribed species of Lygosoma from pitfall traps in an urban rainforest in Kuching and from the base of a forested hill in western Sarawak, East Malaysia. The new species is diagnosable from all south-east Asian congeners by morphological characters, and most closely resembles Lygosoma herberti from the Thai-Malay Peninsula. The new species shows substantial molecular divergence from its closest relatives in two protein-coding genes, one mitochondrial (ND1) and one nuclear (R35) that we sequenced for several south-east Asian congeners. We describe the new species on the basis of this distinct morphology and genetic divergence. It is the third species of Lygosoma known from Borneo, and highlights the continuing rise in lizard species diversity on the island. In addition, the discovery of this species from a small urban rainforest underscores the importance of preserving intact rainforest areas of any size in maintaining species diversity. © Copyright 2018 Magnolia Press.